Peningkatan Kompetensi Guru Pendidikan Agama Islam dalam Perspektif Manajemen Berbasis Madrasah - Shalehuddin Shalehuddin; Rofikatul Maula; Badrul Mudarris; Musolli Musolli (JUMPA : Jurnal Manajemen Pendidikan, 2021)
Abstract: In order to realize the achievement of ideal and professional Islamic Religious Education teachers at MA Darul Lughah Wal Karomah Kraksaan, a managerial approach is needed in order to increase the competence of these teachers, which includes aspects of planning, organizing, supervising. This study uses qualitative research with a descriptive approach. The data collection technique uses; observation, interview and documentation. Data analysis was carried out using data reduction, data display, and conclusion drawing/verification. The validity or validity is carried out by means of data verification, re-checking the report results, and triangulation. The results of research while in the field are as follows; 1) Efforts to increase the competency of Islamic Religious Education teachers at MA Darul Lughah Wal Karomah Kraksaan from a Madrasah-based management perspective are carried out by means of; cultural change, improving the quality of human resources, providing continuous motivation, educational supervision, and continuous evaluation. 2) The results of efforts to increase the competence of Islamic Religious Education teachers in the perspective of Madrasah-based management can be seen in the professionalism of Islamic Religious Education teachers at MA Darul Lughah Wal Karomah Kraksaan which can be seen from; discipline in carrying out duties and responsibilities, improving the quality of teacher human resources, increasing work ethic, and increasing the quality of learning.